(untitled) (LEARNing Landscapes, 2010)
Contemplation plays an important role in developing mindfulness and in preparing us for the work of community in education. Silence, solitude, and the chance to develop one’s sense of self and of purpose are often lost in the fast-paced, technologically driven lives we lead at home and at work. This essay provides a rationale for slowing down and paying attention in order to develop the empathy required to face educational challenges collectively.